Influence of insulin resistance on postoperative period course in patients after colonic anastomosis - M. M. Mylytsia; V. V. Steblianko; T. V. Oliinyk (Zaporožskij Medicinskij Žurnal)
Aim – to determine the influence of insulin resistance (IR) on the development of postoperative complications in patients after application of colon anastomosis (CA).